Desempenho político-eleitoral do Partido dos Trabalhadores, no Espírito Santo, nas eleições de 1982 a 2002 - Oliveira, Ueber José de (2008)
The research refers to the electoral-political performance of the Workers Party (PT) in comparison with similar associations, in Espírito Santo, in the elections occurred between 1982 and 2002. Part of the hypothesis of what PT, in its origin and in its first ten years of existence, took the organization of class as a principal characteristic, to the detriment of the electoral competition. This period is marked by the rise and apogee of PMDB as principal supporting strength. In the next years, specially after the I National Congress carried out in 1991, PT moved gradually to the electoral extent, leaving its line of original acting and becoming a very similar party as the others. In that moment, there took place the obfuscation of a dominant party (PMDB), in circumstances of supporting and ideological fragmentation in the model of political representations. This dissertation agrees with the idea that the principal cause of such a movement of PT bound for the centre of the political specter was the pressure that the current democratic institution practised on the Party, imposing on it determined characteristics that without them the party would obtain good results in the urns. These changes, meantime, produced many internal conflicts in the association, and took it to a weakening in the electoral subsequent processes to 1997.